Effect of Curriculum Modernization on Bed Instructors on Their Educational Achievements and Lifestyle: The Impact of Curriculum Modernization on B.Ed. Instructors' Educational Achievements and Lifestyle (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Education is the key for development of any nation and it depends on the quality of B.Ed. Instructors Lifestyles and Educational Achievements. Knowledge, dedication, quality, professional commitment and motivation of B.Ed. Instructors are responsible for quality education and the achievement of learners. The production of these instructors today is a significant task for governments worldwide. Instructor Educators are responsible for teaching the Instructor's Lifestyles (in addition to the work skills). Acquiring Lifestyles increases Instructors' mental health. Mental wellbeing is a medical duty as well as a personal obligation. This research seeks to create the connection between B.Ed. Instructor’s Lifestyles. Learning success is the criteria attribute and the skills of life are associated with emotional intelligence, stress management, anger and conflict resolution. Today we need well-planned and creative training programs. Criticism, research, redesign, refine and reorientation of the Instructor Education curriculum today must be done.